PROFICIENCY TEST DESIGN: AN EXAMPLE AND ITS ANALYSIS - Umam, Amalul (ENGLISH JOURNAL, 2017)
Understanding language proficiency level of second language learners is very important, because it enables teachers to make plan instruction and assessment to meet the students’ individual needs. In contrast, it is not a simple way to create a proficiency test that can be applicable for all learning contexts. It means that teachers should be able to design their own proficiency test that they can use for their contexts. This study is about designing a proficiency test for certain context. An example is given and administered to the targeted context, and the analysis of the result is discussed.